Benefits and indications of hormone therapy for women in menopause: An integrative literature review (Research, Society and Development, 2024)
Hormone replacement therapy (HRT) acts by replacing ovarian hormones, estrogen and progesterone, significantly alleviating the symptoms that arise during this phase of the female reproductive life and which interfere with the quality of life of many women. Therefore, it is the recommended treatment for most complaints related to this period, varying in terms of its composition, use, and indication. However, they can present significant health risks, contributing to the need for targeted clinical evaluation. The present study aimed to conduct an integrative review to evaluate the indications and benefits of hormone replacement therapy in menopause. Articles published in national and international journals, related to scientific research, were used, including studies published between 2019 and 2024, through the databases National Library of Medicine (PUBMED), Virtual Health Library (BVS), Latin American and Caribbean Literature in Health Sciences (LILACS), COCHRANE, and Scientific Electronic Library Online (SCIELO). After applying the inclusion and exclusion criteria, 13 studies were selected to compose the present review, which aims to explore various available studies regarding the proposed theme. Therefore, understanding the benefits and indications of hormone replacement therapy in menopause is important to provide, safely, better quality of life for women.